Seabed scour induced by a propeller jet - Tan, Remziye Ilayda; Yuksel, Yalcin (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
This paper presents an improvement for the assessment of scour effects due to propeller jet velocities with a direct application to prototype modeling as non-dimensional analysis is conducted. The paper provides insights on the scouring problems due to a propeller jet for a wider of densimetric Froude numbers (1.89 <= Fr-d <= 15.01) condition overcoming limitations found in the literature. Experimental tests were developed for this purpose and formulae recommendations are provided to enhance the estimation of different relevant parameters of the scour process. In this study, the experimental conditions were extended, e.g., ranging from fine to coarse sand beds (d(50) = 0.52 mm, 1.28 mm, 4.00 mm and 8.30 mm), and the Fr-d were compared with previous studies. Hence, this study proposed new formulae to predict scouring due to propeller jet flows. Scaling of the experimental model was explained and experimental conditions are given in the manuscript. An acoustic Doppler velocimeter (ADV) was used to obtain the propeller velocity and in order to calculate the magnitude of efflux velocity a new equation is proposed, where the characteristics of the propeller geometry have been chosen, to improve upon the current level of knowledge in the literature.
Keywords: Scour; Propeller jet; Berth structures; Propeller wash; Water jet; EFFLUX VELOCITY; SHIPS PROPELLER; LOCAL SCOUR; PILE; Engineering; Oceanography